A Hundred Patients of Dr. Jia - Hongjun, Wang (China, 2008)
The director set a static, hidden camera in a small consulting room and persistently followed visits of a hundred of patients who, in the course of 2008, came to consult their ailments (which raises questions as to the documentary ethics) and thus gave a testimony about the diversity in the Chinese society.
Verzio Film Festival Submission
Keywords: Documentary films